Why has there been a 'long peace' in Antarctica? - Julia Jabour (2015)
This article draws on the work of John Lewis Gaddis, a Pulitzer Prize-winning author and historian particularly well known for his scholarship on the Cold War. In his 1986 paper, “The Long Peace: Elements of Stability in the Postwar International System” Gaddis posited a range of plausible reasons for why neither the United States nor the Soviet Union took the ultimate step of initiating a nuclear war against the other. This restraint was founded on principles of mutual understanding of the consequences of such an action and contributed to what he termed the ‘long peace’ in post-Cold War international relations. This article examines why there has also been a ‘long peace’ in Antarctic relations, using Gaddis’s theories and applying them to the Antarctic Treaty Consultative Parties’ dealings with each other in the context of the Antarctic Treaty System – the legal regime that governs Antarctica. It finds that despite a radically different set of international relations circumstances today, Gaddis’s theories hold true. How long this long peace will last is not the point here; merely that it exists is cause for optimism.